Daughter of Writing Mother Writ Large with Hélène Cixous - Jordan, Nané (Journal of the Motherhood Initiative for Research and Community Involvement, 2017)
This essay explores Hélène Cixous’s use of maternal generative processes, especially birth-giving subjectivities, as the basis for new conceptions of writing. I then expand upon aspects of the mother daughter relationship at the heart of a series of Cixous’s recent novels or fictions. Hélène Cixous’s oeuvre includes feminist literary and poetic- theoretic essays, novels, and theatre pieces. She is most famous in North America for her 1976 essay “The Laugh of the Medusa.” Yet further translations of Cixous’s prolific works are less known to English readers. I hope to reevaluate Hélène Cixous as an important writer in the field of motherhood studies and beyond. Although maternal subjectivities are still often unwritten and undervalued grounds, with Cixous, mothers and daughters are central texts for living and art. In Cixous, “Mother,” writ large, becomes fused with the act of writing. Mother is a double figure who occupies both life and art—the progenitor of both. She is perhaps the Mother of all books, so that Cixous is surely the daughter of writing.